The Implemetation of Accountability in Realizing Good Governance in Bintan Regency - Puji Lestari (Jurnal Studi Pemerintahan dan Akuntabilitas, 2026)
Abstract Purpose: The purpose of writing this policy paper is to analyse the implementation of the principle of accountability by identifying the obstacles or issues faced in order to enhance accountability in the effort to achieve good governance in Bintan Regency. Methodology/approach: The research method used in the preparation of this Policy Paper is qualitative research. The data is analysed descriptively in a qualitative manner. Qualitative data analysis is inductive, meaning it is analysis based on the data obtained. Results/findings: This policy paper produces policy recommendations by formulating policies in the form of a Regent Regulation on the Implementation Guidelines for SAKIP, which includes procedures for setting performance indicator targets and strategic objectives of the Regional Device, and also explains the alignment between performance planning documents. Conclusion: There are four issues that cause the performance accountability not to be suboptimal: 1) The quality of planning is not yet optimal; 2) Performance measurement has not been conducted comprehensively down to the lowest units; 3) Performance reports have not been prepared completely and do not present adequate data; 4) Evaluation of the implementation of SAKIP has not been carried out in a deep or comprehensive manner. Limitations: The collection of primary data through interviews where, despite efforts to maintain objectivity, the interview results still contain elements of subjectivity from the informants that can influence data interpretation. Contribution: This policy recommendation can be used as a basis for formulating policies related to increasing the accountability of the Bintan regency government.